Implementing laboratory quality management systems in Ghana: A quality audit of accreditation readiness in clinical and public health laboratories (2021–2023) - Emma E. Kploanyi; David W. Dowdy; Joseph Kenu; Benjamin Buade; Benedicta Owusu-Arthur; David A. Opare; Franklin Asiedu-Bekoe; Alfred E. Yawson; Ernest Kenu; Lee F. Schroeder (African Journal of Laboratory Medicine, 2026)
Background: The Stepwise Laboratory Improvement Process Towards Accreditation (SLIPTA) checklist has demonstrated improvement in laboratory quality in Africa. In Ghana, however, implementation has targeted mainly higher-tier clinical laboratories. A balanced approach across the laboratory network is needed to strengthen national laboratory quality. Objective: To evaluate the quality management performance and accreditation readiness of clinical and public health laboratories (PHLs) in Ghana. Methods: Using a modified SLIPTA checklist, we audited randomly selected clinical and PHLs from districts in the three ecological zones from February 2021 to November 2023. Analyses employed Wilcoxon rank-sum tests, Kruskal-Wallis tests, and quantile regression to assess associations between laboratory characteristics and SLIPTA scores. Results: Forty-five health facilities and four PHLs were audited: 80% of facilities were in the public sector. Laboratories performed a median of 24 (Interquartile range [IQR]: 10–70) tests daily. The median SLIPTA score was 50% (IQR: 35% – 58%), with hospitals recording the highest scores [median, IQR: 58% (51% – 61%)]. Of the 12 SLIPTA quality systems essentials, laboratories performed highest in organisation and personnel. In multivariable regression, facility location in the Northern zone (adjusted coefficient = –23, 95%CI = –38 to –8; p < 0.001) was negatively associated with SLIPTA scores compared to the Southern zone. Conclusion: More hospitals and PHLs had achieved a minimum one-star rating towards International Organization for Standardization accreditation readiness during the quality audit. Persistent gaps in client management, internal audits, and corrective actions require targeted training and mentoring to support effective implementation of improvement initiatives. What this study adds: This study provides the first nationwide quality audit of a representative sample of clinical laboratories and PHLs in Ghana with a balanced representation of health facilities in the tiered laboratory network, underscoring the need for a more inclusive, sustainable approach to laboratory quality improvement across the tiered network of the country.